(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
In the theory of thermoelasticity, problems are typically solved in terms of stress by introducing Airy’s stress functions. However, in this work, the problem of thermoelasticity is formulated and solved directly in terms of stresses in a spatial setting, without introducing any additional functions. The algorithm for the solution is also presented.